2021
DOI: 10.1016/j.cegh.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological status of suicide in the Middle East and North Africa countries (MENA) from 1990 to 2017

Abstract: Background Suicide is proposed as an important and growing issue in public health. The aim of this study is to compare suicide load in the Middle East and North Africa (MENA) countries in order to pave the way for correct health policy making. Methods The population included 21 MENA countries. The data of Global Burden of Diseases in 2017 that estimate death rate for 264 causes was used. The GBD considers suicide according to definition of the ninth and tenth editions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Usually, HTN has no symptoms, and various causes developing it, but it can be controlled with medications [ 1 ]. The prevalence of HTN in different countries varies from 10% to more than 60% [ 2 ], and its average global prevalence is reported about 22% in 2021 [ 3 ]. Based on the evidence, the prevalence of HTN will be increased to 29.2% in 2025 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, HTN has no symptoms, and various causes developing it, but it can be controlled with medications [ 1 ]. The prevalence of HTN in different countries varies from 10% to more than 60% [ 2 ], and its average global prevalence is reported about 22% in 2021 [ 3 ]. Based on the evidence, the prevalence of HTN will be increased to 29.2% in 2025 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Some studies on the epidemiology of mental disorders have been published in recent years. 6 , 8 , 9 , 10 , 11 However, these studies have mainly focused on individual disorders. To date, no study has investigated the total burden of mental disorders in the MENA region.…”
Section: Introductionmentioning
confidence: 99%
“…Though suicide prevalence rates in the Arab World may vary by country (Naghavi, 2019 ), there appear to be certain commonalities based on individuals’ age. Rates of death by suicide are highest for people under the age of 30, comprising 38.6% of all deaths by suicide (Naghavi, 2019 ), with the greatest prevalence of suicidal behavior among those aged 20–24 (Amini et al, 2021 ). Indeed, Eskin and colleagues ( 2019 ) found that 22% of university students living in predominantly Muslim Mediterranean countries reported suicidal ideation and 8.6% reported attempting suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Alarmingly, some studies suggest that suicidality may occur even earlier, with 28.9% of Lebanese adolescents reporting suicidal ideation (Chahine et al, 2020 ). Beyond young adulthood, suicide rates decrease with age, and then increase again for people over age 65 (Amini et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%